EFFECTS OF ORAL ADMINISTRATION OF PHYLLANTHUS AMARUS LEAF EXTRACT ON THE KIDNEYS OF ADULT WISTAR RATS- A HISTOLOGICAL STUDY - Andrew, Eweka Osayame; Enogieru, Adaze (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Abstract Histological studies of the effects of oral administration of aqueous extract of Phyllanthus amarus commonly used in ethno medical practice in Africa for the management of various ailments such as kidney stones, dysentery, jaundice, diarrhoea and urogenital diseases on the kidney of adult Wistar rats were carefully studied. Rats of both sexes (n=24), average weight of 260g were randomly assigned into three groups: A, B and C of (n=8) in each group. Group A and B served as treatment groups (n=16) while group C (n=8) served as the control. The rats in the treatment groups (A & B) received 500mg/kg body weight and1000mg/kg body weight respectively of aqueous extract of Phyllanthus amarus orally through orogastric tube for twenty-eight days, while the control rats received equal volume of distilled water without the extract of Phyllanthus amarus added for the same period. The rats were fed with growers’ mash purchased from Edo feeds and Flour Mill Ltd, Ewu, Edo state and were given water liberally. The rats were sacrificed on day twenty-nine of the experiment. The kidneys were carefully dissected out and quickly fixed in 10% formal saline for routine histological study after H&E method. The histological findings indicated that the treated sections of the kidneys showed hypertrophy of blood vessels, mild-severe infiltrate of chronic inflammatory cells and varying degrees of tubular necrosis when compared to the control sections. The findings indicated that the administration of Phyllanthus amarus extract has some adverse effects on the kidneys of adult Wistar rats. It is recommended that further studies aimed at corroborating these observations be carried out.